2007
DOI: 10.1186/1742-4690-4-66
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and immunogenicity of attenuated, nef-deleted HIV-1 strains in vivo

Abstract: In efforts to develop an effective vaccine, sterilizing immunity to primate lentiviruses has only been achieved by the use of live attenuated viruses carrying major deletions in nef and other accessory genes. Although live attenuated HIV vaccines are unlikely to be developed due to a myriad of safety concerns, opportunities exist to better understand the correlates of immune protection against HIV infection by studying rare cohorts of long-term survivors infected with attenuated, nef-deleted HIV strains such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 103 publications
0
80
0
Order By: Relevance
“…Soon after its initial description as a negative factor of HIV-1 replication (3,54,63), Nef was shown to be required for optimal HIV and SIV infectivity in vitro and pathogenicity in vivo (4,9,18,28,37,39,40,46,47,71). Several mechanisms have been put forward to explain the gain of infectivity conferred by Nef to HIV-1; however, these mechanisms fail to fit all the experimental systems in which the gain of infectivity can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soon after its initial description as a negative factor of HIV-1 replication (3,54,63), Nef was shown to be required for optimal HIV and SIV infectivity in vitro and pathogenicity in vivo (4,9,18,28,37,39,40,46,47,71). Several mechanisms have been put forward to explain the gain of infectivity conferred by Nef to HIV-1; however, these mechanisms fail to fit all the experimental systems in which the gain of infectivity can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, Nef has proven to play a major role in the progression of infections with simian (SIV) and human (HIV) immunodeficiency viruses toward AIDS in primates (18,28,39,40,46,47,71). Single-round infection assays based on cell-free recombinant viruses also revealed that wild-type (WT) HIV type 1 (HIV-1) and SIV are more infectious than mutants lacking Nef expression (⌬nef viruses) (4,9,37).…”
mentioning
confidence: 99%
“…During the early stages of infection, one of the most abundantly produced HIV proteins is Nef, an accessory protein with no enzymatic activity. Nef is a 27-35-kDa myristoylated protein encoded by the HIV-1, HIV-2 and the simian immunodeficiency virus (SIV) genomes, which is crucial for sustaining robust viral production and promoting disease progression to full-blown AIDS (Deacon et al, 1995;Gorry et al, 2007;Gulizia et al, 1997;Kestier et al, 1991;Learmont et al, 1999;Oelrichs et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nef, an HIV-1 accessory protein, is expressed abundantly in the early stages of the viral life cycle and plays a key role in the progression of infection toward AIDS in primates (13)(14)(15). Among Nef functions, its ability to affect cell surface protein trafficking, including CD4 or MHC I molecules, has been well characterized (16).…”
mentioning
confidence: 99%